Forest Resource Management using Remote Sensing and GIS in Chandraprabha Basin - Mishra, Kavita; Kumra, V.K. (National Geographical Journal of India, 2022)
Forests are considered as most important renewable resources. A productive, protective and aesthetic value of forest signifies it as green gold. The remotely sensed data have proved strong data base for forest mapping, inventory and monitoring its changes with reasonable accuracy both in the temporal and spatial framework. Present paper is an attempt to analyze different types of forest resources and their management in Chandraprabha basin, Eastern Uttar Pradesh. Remotely sensed data of IRS - P6, LISS - III (geocoded FCC) product has provided good depth of information for identifying and delineating the four types of forest in the study area, i.e., dense forest, open forest, scrubs/bushes and plantation.